Candidate avirulent effector protein 2565 reduces clubroot incidence via rhizosphere microbiome restructuring and root exudate modulation - Wang, Diandong; Liao, Jingjing; Shi, Jiayu; Cai, Zhaoming; Luo, Luyun; Chen, Tailin; Zhang, Yixi; Tian, Xue Liang (Frontiers in Microbiology, 2025)
Clubroot disease caused by Plasmodiophora brassicae in tumorous stem mustard (Brassica juncea var. tumida) is difficult to control. Avirulent effector proteins can trigger plant immunity to fight pathogens, which exhibits promising prospect for managing this disease. Building on our earlier discovery that candidate avirulent effector protein 2565 reduces clubroot, this study used high-throughput sequencing and metabolomics to reveal the mechanisms at the microbiome and metabolome levels. Results showed that protein 2565 changed the beta diversity of rhizosphere bacterial communities and increased the abundance of Paenibacillus and Terrabacter. Additionally, this protein modified root exudates, leading to higher levels of disease-resistant metabolites like geniposidic acid and 8-hydroxyluteolin glucuronide. The close connection between microbial changes and metabolite shifts was confirmed by Procrustes analysis (M2 = 0.300, p = 0.001), indicating that protein 2565 both alters the root exudates and rhizosphere bacterial community to enhance plant defenses. Our findings highlight the potential of avirulent effectors in sustainable disease management through metabolic-microbial interaction.